1981
DOI: 10.1002/hlca.19810640518
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Open‐Chain 2,3‐Disubstituted 4‐nitroketones by Diastereoselective Michael‐addition of (E)‐Enamines to (E)‐Nitroolefins. A topological rule for C, C‐bond forming processes between prochiral centres. Preliminary communication

Abstract: The Michael‐additions of aliphatic, alicyclic, and arylsubstituted nitroolefins and enamines lead to γ‐nitroketones 3 in good chemical and excellent (> 90%) diastereomeric yields (see Table 1). The known threo‐configuration of one type of adducts 3 (entries 8, 10, and 11 of Table 1) can be arrived at by assuming the approach 8 of the Michael‐acceptor and ‐donor; the reaction follows a topological rule, which is formulated and which is applicable to such diverse reactions as the diene synthesis, cyclopropanatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
2
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 391 publications
(139 citation statements)
references
References 85 publications
(22 reference statements)
10
119
2
6
Order By: Relevance
“…iv) The relative topicity of addition to the enamine C¼C bond follows the topicity rule for the coupling of trigonal centers [45] as shown for the aldol addition in C and for the Michael addition in D, which invariably 35 ) occur with relative topicity lk (Re/Re).…”
Section: Methodsmentioning
confidence: 85%
“…iv) The relative topicity of addition to the enamine C¼C bond follows the topicity rule for the coupling of trigonal centers [45] as shown for the aldol addition in C and for the Michael addition in D, which invariably 35 ) occur with relative topicity lk (Re/Re).…”
Section: Methodsmentioning
confidence: 85%
“…Preliminary studies showed that, as expected, the initial formation of an enamine between catalyst and aldehyde is followed by the nucleophilic attack to the maleimide, according to Seebach's synclinal model (endo attack, Figure 1). [31] A key feature of this model is that the reacting face of the enamine diastereoespecifically attacks only one of the faces of the maleimide. That is, the lower face of the enamine (from our point of view in Figure 1) is reacting with the Re-face of the maleimide, and the upper face of the enamine must react with the Si-face of the maleimide.…”
Section: Resultsmentioning
confidence: 99%
“…The observed linearity suggested that the active catalyst in this process is a monomeric species. [44] The syn-diastereoselectivity and the absolute configuration observed can be reasonably explained through the acyclic synclinal transition state assembly A proposed by Seebach, [45] assuming intramolecular hydrogen bonding (Scheme 8). …”
Section: Scheme 7 Michael Addition Of Butanone To Trans-β-nitrostyrenementioning
confidence: 83%